PARAMETERS OF FRAME REPRESENTATIONS OF LINGUOCULTUREMES (Scientific journal of the Fergana State University, 2023)
This article reveals the issues of frame representations of one of the basic concepts of linguoculturological science – linguoculturemes, which are used to denote cognitive units. This term is also actively used in various fields of science, such as artificial intelligence, knowledge engineering, social sciences, publishing systems, telecommunications, computer networks, programming, videography. As you know, frames are an economical way of transmitting information, speeding up the process of its processing, since they contain explicit and hidden, implied information. This paper presents the process of preparing the "Russian-Uzbek dictionary of frame representations of linguoculturemes" based on the results of scientific research, as well as a fragment of its dictionary entry.